Test to evaluate knowledge in Law: analysis of the items by applying the Rasch model - Belén Ghio, Fernanda (2019)
The evaluation of the academic performance of university students is a fundamental element to measure the quality of education in a higher education. The most direct way to obtain this qualification is through exams or probing tests, however if we consider that teachers are the ones who determine the form of evaluation, these instruments may present shortcomings in their elaboration. Therefore, in the School of Psychology of the National University of Cordoba is being built a test that attempts to estimate the academic performance of university students. Reason for which in this work the Rasch model is applied to evaluate the psychometric properties of 31 items of Level I of the knowledge domain in Laws. The sample consisted of 170 students aged between 19 and 60 years (M = 24.59, DE = 6.22). In general, the items have good psychometric properties. This work makes significant contributions in the field of measurement and evaluation in our environment, based on the need to evaluate the wide range of knowledge and skills that students must achieve in the university environment.